Analisis Pengaruh Bauran Pemasaran terhadap Penjualan - Nana Sopiana (Postgraduate, University of Mataram, 2021)
The purpose of this study is to prove the significance of the influence of the marketing mix both simultaneously and partially on the sale of coffee products and prove the marketing mix that has a dominant influence on the sale of coffee products in coffee companies and convection